SEROLOGICAL SURVEY OF TOXOPLASMOSIS, NEOSPOROSIS AND BRUCELLOSIS AMONG CATTLE HERDS IN OYO STATE, SOUTH-WESTERN NIGERIA - Ayinmode, Adekunle; Akinseye, Victor; Schares, Gereon; Cadmus, Simeon (African Journal of Infectious Diseases (AJID), 2017)
Background: Several zoonotic diseases are known to constitute great impediment to livestock management and production worldwide, especially in developing countries where control measures are largely non-existent. This study sets out to investigate the occurrence of toxoplasmosis, neosporosis and brucellosis among cattle herds in Oyo State, southwest Nigeria. Materials and Methods: A cross-sectional survey to screen for antibodies to Toxoplasma gondii, Neospora caninum and Brucella abortus was conducted among 174 cattle in 17 herds. Sera obtained from the cattle were screened for antibodies to Toxoplasma gondii and Neospora caninum using enzyme-linked immunosorbent assay (ELISA) and for Brucella abortus antibodies using Rose Bengal test and Competitive Enzyme Linked Immunosorbent Assay (cELISA). Results: Overall, herd level prevalence of 52.9%, 23.5% and 23.5% as well as individual prevalence of 7.5%, 3.4% and 3.4% was obtained for toxoplasmosis, neosporosis and brucellosis, respectively. Antibodies to T. gondii, N. caninum and B. abortus were detected in 2 of the 17 herds, T. gondii and N. caninum in 4 herds, and T. gondii and B. abortus in 4 herds. Statistically significant association was only found between seropositivity to T. gondii antibodies and sex (p<0.05). Conclusion: Our results showed that toxoplasmosis, neosporosis and brucellosis are prevalent among cattle herds screened in the study area. Considering the potential impact of these diseases on livestock management and production, extensive surveillance is necessary for development and implementation of effective control and prevention strategies.